A quantitative study of the plankton and physico-chemical conditions of the River Jumna at Allahabad in 1954-55 - Chakrabarty, R D; Roy, P; Singh, S B (Indian Journal of Fisheries, 2016)
The productivity of a river or a stream has a direct bearing upon the welfare of fish life and the role of plankton in the tropic cycle has been well recognised. Not much of work has been done on plankton production of any of the major rivers of India, although Chacko and Ganapati (1949) and Chacko et al. (1953) have contributed some information on certain aspects of plankton of rivers Adyar and Malampuzha. Observations were therefore made in the river Jumna at Allahabad to study the abundance, seasonal fluctuations and diurnal variation of plankton in relation to physico-chemical conditions of water. The present paper communicates the results of these studies made in the years 1954-55.